Herbivores alleviate the negative effects of extreme drought on plant community by enhancing dominant species. (17th June 2021) - Xu, Chong; Ke, Yuguang; Wu, Honghui; Smith, Melinda D; Lemoine, Nathan P; Zhang, Weiguo; Yu, Qiang
Abstract: Aims: Both extreme drought and insect herbivores can suppress plant growth in grassland communities. However, most studies have examined extreme drought and insects in isolation, and there is reason to believe that insects might alter the ability of grasslands to withstand drought. Unfortunately, few studies have tested the interactive effects of extreme drought and insect herbivores in grassland communities. Methods: Here, we tested the drought–herbivore interactions using a manipulative experiment that factorially crossed extreme drought with the exclusion of insect herbivores in a temperate semiarid grassland in Inner Mongolia. Important Findings: Our results demonstrated that both extreme drought and insect herbivores separately decreased total plant cover. When combined, insect herbivores reduced the impact of drought on total cover by increasing the relative abundance of drought-resistant dominant species. Our results highlight that the negative effect of extreme drought on total plant cover could be alleviated by maintaining robust insect herbivore communities.